Philosophical and Speculative Economies of the Vanishing Body - Kolozova, Katerina (Frontiers in Sociology, 2018)
The human is materially determined by that “irrational” hybrid of the physical and machine resulting in no more and no less sense than the “pure body” (if such thing is possible beyond mere postulation) is endowed with. The “rational” part of it or the “agency of making sense” remains outside the materiality of either the body or the machine – it is the automaton of signification or language. The automaton of capital and philosophy is individually substantiated as “subjectivity,” and more specifically that of the split capitalist self. The hybrid consisted of the physical (natural and machinic), on the one hand, and of the subject of signification, on the other hand, is the monstrosity that ultimately escapes sense: it is inhuman (Haraway) or non-human (Laruelle). It is that inhuman inanity that is neither subject nor merely body nor just a machine, the non-human. Similarly to Donna Haraway’s claim about the radical constructedness of the human as cyborg (Haraway, 1985), Marx argued that sociality, which includes both economic production and the so-called social reproduction (via the means of production), on the one hand and physicality on the other hand constitute the species-being of humanity. The human is radically constructed, yet, in the last instance, determined by the physical, argue both Haraway and Marx.